Defining Death Anew: Reexamining the Twentieth-Century Brain Death Debates and the Uniform Determination of Death Act - Clinton, Anne E. (The Hastings Center report, 2025)
In the twentieth century, following the development of advanced life-support technology, recognition of perimortem states such as brain death challenged traditional definitions of death. A series of debates in the 1960s and 1970s regarding the need to adapt the social and legal frameworks in the face of new medical capabilities culminated in the publication and widespread adoption of the Uniform Determination of Death Act. However, in the interests of uniformity, the drafters of the UDDA compromised its internal conceptual clarity in favor of ensuring that the UDDA was broadly acceptable. A uniform statute proposed by James Bernat and collaborators in the 1980s demonstrates that increased clarity regarding underlying philosophical commitments in a model statute could help to resolve this confusion.